IMPLEMENTASI METODE SCRUM PADA PERANCANGAN SISTEM INFORMASI TATA USAHA SEKOLAH BERBASIS WEB - Mardika, Putri Dina; Ahmad Fauzi; Nilma (Lembaga Pengembangan Kinerja Dosen, 2022)
The use of information technology which is increasingly becoming an important need for all sectors of people's lives with all the conveniences offered such as speed and good data processing accuracy makes this difficult for today's society to do. In the world of education, information technology is also used in data processing in the administrative section. MTs Sirojul Athfal which still uses conventional methods, needs an information system to process student payment data so as to reduce errors in data processing. The Scrum method is very well used in the process of making information systems that require fast time to implement. The purpose of this research is to implement the SCRUM method in the design of the MTs Administrative Information System. The results of this study indicate that the SCRUM method is very well used in the manufacture of Information Systems, which requires fast time and needs dynamic information systems in the process.